Construction and preliminary testing of a guarded hot plate apparatus for thermal conductivity measurements at high temperatures. (July 2018) - Yang, Inseok; Kim, Daeho; Lee, Sanghyun
Highlights: A guarded hot plate apparatus that can be operated up to 1000 °C was constructed. Preliminary thermal conductivity measurements up to 800 °C are presented. The lateral heat flow across the air gap was actively compensated for. The apparatus showed linearity within 0.5% for various temperature differences. Abstract: We constructed a guarded hot plate (GHP) apparatus that can be used for thermal conductivity measurements from 100 °C to 1000 °C. The apparatus measures the effective thermal conductivity of square-shaped thermal insulation materials of 300 mm per side in a controlled gas environment. As a preliminary test for the high temperature GHP apparatus, we first measured the amount of electrical power required for heaters at various locations to maintain the temperature at up to 900 °C. After this, two specimens of thermal insulation material whose thermal conductivities are ≈0.044 W·m –1  K –1 and ≈0.025 W m –1  K –1 at room temperature were tested at a thermally steady state with unilateral heat flow at temperatures between 100 °C and 800 °C. We applied an offset to the guard plate to actively compensate for the lateral heat flow across the air gap. The measurements showed that the linearity between the temperature difference on the two sides of the specimen and the power dissipated across the specimen was extremely good (with a standard deviation of 0.1%). After some modifications suggested from the preliminary test, we expect that the high temperature GHP will work within the technical specification CEN/TS 15548-1:2014 in the range up to 800 °C, but rigorous uncertainty assessment is yet to be performed after such modifications.